Institutional Risk in Child Protection: Perspective of Professionals - Ilona Tamutienė; Vaida Auglytė (Public Policy and Administration, 2018)
This article focuses on institutional risk factors that relate to the ability of child rights professionals to protect maltreated children. The aim of the article is to reveal the structural threats existing in the system of protection of the child’s rights, which create preconditions for the disclosure of institutional risks. Semi-structured qualitative interview method used. Ten interviews with children's rights protection specialists (CRPS) conducted during March-April 2018. According to the content analysis method, it has been established that the family assistance model for child protection is declarative in nature, due to the lack of services that meet the needs of children and families, and poor accessibility and quality, especially in rural areas, and social work orientation into control. The findings highlighted gaps in inter-agency cooperation in the protection of the child, the low level of involvement of health care, in particular – the treatment of paediatric and addictive diseases. In view of the internal field of the childʼs rights services, it has been highlighted that institutional problems are significantly contributing to the institutional risk: CRPS experienced inadequate methodological assistance and training which not corresponding to the problems encountering in everyday practice, lack of human resources, large workloads, low wages, lack of working methods, lack of stress management. In the context of the ongoing reform of the protection of the rights of the child, it is recommended to eliminate institutional risks, to strengthen services for children and families, and to improve inter-agency cooperation in the protection of the child.